Back to Surau: Redefining Early Childhood Character Education Through the Lens of Minangkabau Culture - Syafrida, Rina; Riana, Nancy; Karnia, Nia; Ismail, Marzeni (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2025)
Purpose – This study aims to explain the rationale behind the